Accurate Measurement of First Metatarsophalangeal Range of Motion in Patients With Hallux Rigidus. (May 2016) - Vulcano, Ettore; Tracey, Joseph A.; Myerson, Mark S.
Background: The reliability of range of motion (ROM) measurements has not been established for the hallux metatarsophalangeal (MTP) joint in patients with hallux rigidus. The aim of the present study was to prospectively assess the clinical versus radiographic difference in ROM of the arthritic hallux MTP joint. Method: One hundred consecutive patients who presented with any grade of hallux rigidus were included in this prospective study to determine the hallux MTP range of motion. Clinical range of motion using a goniometer and radiographic range of motion on dynamic x-rays was recorded. Results: The mean difference between clinical and radiographic dorsiflexion was 13 degrees ( P < .001). For all measurements, clinical dorsiflexion was equal to or less than radiographically measured dorsiflexion. The difference was significantly greater in patients with a clinical dorsiflexion of less than 30 degrees than in patients with 30 degrees or more. Radiographic measurement of hallux dorsiflexion had an excellent intra- and interobserver reliability. Conclusion: We describe a reliable, reproducible, and straightforward method of measuring hallux MTP ROM that improved upon measuring clinical ROM. Level of Evidence: Level II, prospective comparative study.